1993
DOI: 10.1113/jphysiol.1993.sp019638
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nerve growth factor on neuronal plasticity of the kitten visual cortex.

Abstract: SUMMARY1. The effect of intraventricular administration of nerve growth factor (NGF) by means of a cannula-minipump system was studied in kittens monocularly deprived during the critical period. The ocular dominance of area 17 neurones of NGF-treated and control kittens was determined by conventional extracellular recordings. The soma size of cells in A and Al laminae of the lateral geniculate nucleus (LGN) was also evaluated in Cresyl Violet preparations.2. Binocularly responsive neurones were found to be sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
59
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 100 publications
(60 citation statements)
references
References 39 publications
1
59
0
Order By: Relevance
“…al., 1992), a similar protocol in the kitten merely attenuated the physiological shift in ocular dominance induced by MD (Carmignoto et al, 1993). In addition, local delivery of NGF had no e¡ect on ocular dominance column formation in the kitten (Figs.…”
Section: Brief Local Cortical Infusion Of Ngf Has No E¡ect On Ocular mentioning
confidence: 90%
See 4 more Smart Citations
“…al., 1992), a similar protocol in the kitten merely attenuated the physiological shift in ocular dominance induced by MD (Carmignoto et al, 1993). In addition, local delivery of NGF had no e¡ect on ocular dominance column formation in the kitten (Figs.…”
Section: Brief Local Cortical Infusion Of Ngf Has No E¡ect On Ocular mentioning
confidence: 90%
“…3 and 4, the NGF was infused only for 2 or 3 days before the beginning of deprivation, and previous studies of the kitten started NGF infusion and MD at the same time (Carmignoto et al, 1993;Galuske et al, 2000). However, other experiments have suggested that delivery of exogenous NGF can produce e¡ects that require a period of days or even weeks to be expressed.…”
Section: Prolonged Ngf Infusion Has No E¡ect On Ocular Dominance Plasmentioning
confidence: 99%
See 3 more Smart Citations